Waiting for Christmas [large type] - Austin, Lynn N. (Gilded Age story, 2024)
"For the first time in her privileged life, Adelaide Forsythe won't be swept up in the hustle and bustle of the holidays descending on New York's Fifth Avenue. She couldn't be happier about the prospect of a quieter Christmas. That's not to say her transition from Miss to Mrs. has been without challenge. Though she doesn't regret marrying for love instead of wealth, she can barely light the hearth or cook more than burnt toast. She feels woefully unprepared to run her own household. Then, on the first Sunday of Advent, winter winds bring change through two unlikely means: a young orphan boy, hiding near Adelaide's front steps, and a seasoned housekeeper who seems too good to be true. The boy, Jack, claims he isn't an orphan at all and is desperate to reunite his family. Adelaide and her husband Howard work tirelessly to solve the riddle of Jack's story, while Adelaide's new endeavors open her eyes to a world beyond her past experience -- and all the challenge and possibility it holds. As Christmas approaches, small glimmers of wonder light the way toward the answers Adelaide seeks and the most miraculous gift of all."--